2017
DOI: 10.1093/geront/gnx183
|View full text |Cite
|
Sign up to set email alerts
|

The Tele.TAnDem Intervention: Telephone-based CBT for Family Caregivers of People With Dementia

Abstract: The CBT-based telephone intervention increased mental and physical health as well as coping abilities of family caregivers of people with dementia. The intervention can be delivered by qualified CBT therapists after an 8-h training session in existing health care provision structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 72 publications
(133 citation statements)
references
References 51 publications
7
122
0
2
Order By: Relevance
“…Nonsignificant effects on caregiver burden are also a frequent finding in intervention studies with dementia caregivers (Wasilewski et al, ; Wilz, Reder, et al, ). In fact, a major challenge of interventions for caregivers is that the caregiving situation is becoming increasingly difficult with time and any intervention that has a fixed ending might not be sufficient to lift caregiver burden.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Nonsignificant effects on caregiver burden are also a frequent finding in intervention studies with dementia caregivers (Wasilewski et al, ; Wilz, Reder, et al, ). In fact, a major challenge of interventions for caregivers is that the caregiving situation is becoming increasingly difficult with time and any intervention that has a fixed ending might not be sufficient to lift caregiver burden.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, 26.7% of study participants rated eight messages as not enough and the most successful intervention programs consist of 10 or more sessions (e.g., Belle et al, ; Mittelman, Roth, Coon, & Haley, ). In the 12‐session telephone‐based Tele.TAnDem intervention, participants improved on a wide range of outcomes including symptoms of depression (Wilz, Reder, et al, ), but fewer effects were found for the seven‐session Tele.TAnDem program (Wilz & Soellner, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations